PENGARUH KREDIBILITAS BANK, PERSEPSI KEMANFAATAN DAN PERSEPSI KEMUDAHAN APLIKASI PERBANKAN TERHADAP MINAT NASABAH MENGGUNAKAN LAYANAN BSI MOBILE DI BANK SYARIAH INDONESIA KCP PONOROGO SOETTA - Nur Hayati; Ajeng Pipit Fitriani (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2023)
Customer interest is the desire to try the product and an interest arises in using and owning the product. Customer interest can be influenced by several factors including the bank's credibility, perceived usefulness and perceived convenience. Bank credibility is a form of customer trust in banking, the behavior of someone who believes their transactions and privacy are safely guarded by banks. Perceived usefulness is a person's subjective view if using an information technology can improve performance. Perceived convenience is the degree to which a person believes that using a system does not require much effort. This study uses a quantitative research approach using primary data obtained through interviews and distributing questionnaires. The population used in this study are customers who use the BSI Mobile application at Bank Syariah Indonesia KCP Ponorogo Soetta whose number is unknown. The sampling technique in this study used the Lemeshow formula with 100 respondents as the research sample. The data analysis method used in this study is multiple linear regression analysis. The results of this study indicate that: Bank credibility, perceived usefulness and perceived convenience partially and simultaneously have a significant effect on customers' interest in using BSI Mobile services at BSI KCP Ponorogo Soetta.